Implementation of Android-Based Crossword Educational Model as an Effort to Improve Dental Health Maintenance Behavior of Elementary School Children - Bedjo Santoso; Supriyana Supriyana; Bambang Sutomo (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2024)
Oral health is an integral part of overall body health. Clinical factors that cause dental caries in elementaryschool children are influenced by host, substart and time. Oral hygiene needs to be maintained from anearly age, especially in children in primary school. If this hygiene is neglected, it can have a negative impacton the child's debris index score. The School Dental Health Program (UKGS) aims to improve the dentalhealth of students in schools through various activities that are promotive, preventive, and curative forstudents who need treatment. One of the effective dental health education methods to be given to elementaryschool children is through crossword puzzles. The method of implementing this community service iscarried out by demonstration, training and assistance in brushing teeth in elementary school children. Basedon the results of community service carried out at SD Negeri Cepoko, it can be concluded that there is anincrease in children's behavior, attitudes and actions towards maintaining dental health and a decrease inthe debris index score in children.Keyword : dental health, children, brushing teeth